FRI0355 MUCOSAL ASSOCIATED INVARIANT T-CELLS ARE ENRICHED AT THE HUMAN ENTHESIS AND HAVE A RESIDENT MEMORY PHENOTYPE. (June 2019) - Cuthbert, Richard; Zhou, Qiao; Watad, Abdulla; Dunsmuir, Robert; Loughenbury, Peter; Khan, Almas; Millner, Peter; Bridgewood, Charlie; Mcgonagle, Dennis
Abstract : Background: Mucosal associated invariant T-cells (MAITs) are innate-like T lymphocytes that express a semi-invariant TCR repertoire. They are activated by microbial ligands or cytokines including IL-23 and secrete inflammatory cytokines, including IFNγ and IL-17A. MAIT cells are enriched at mucosal surfaces and have been implicated in the pathogenesis of spondyloarthritis (SpA) (1) and inflammatory bowel disease (IBD). Although the human enthesis is not a mucosal surface it is the primary site of inflammation in SpA which has strong association with IBD. Objectives: To investigate if a population of MAITs is present at the normal human enthesis thereby establishing a potential link between gut and joint inflammation. Methods: Healthy interspinous ligament and spinous process were harvested from patients undergoing elective surgery for the correction of mechanical spinal defects. Entheseal soft tissue (EST) and peri-entheseal bone (PEB) were separated and cells were harvested by enzymatic and mechanical digestion respectively. The proportion of cells expressing markers consistent with MAITS (CD45+, CD3+, CD161+, TCRVα7.2+) were measured by flow cytometry in EST, PEB and matched blood. Expression of CD69 and CD45RA were examined for phenotypic analysis. Transcript analysis for IL-23/IL-17 axis and immunomodulatory genes was performed on sorted entheseal MAITs and analysed by TaqMan array. Results: As a proportion of total T-cells, MAITs were of approximately 3 fold and 2.5 fold greater abundance in EST and PEB respectively in comparison to matched peripheral blood (both p=0.034). MAITs in entheseal tissue had an overwhelming resident memory phenotype (CD69+, CD45RA-) median 53.2% (range 42.4 – 78.6%) in EST and 54.9% (45.2 - 82.1%) in PEB compared to those from blood 17.7 (6.8 – 69.4). MAITs robustly expressed RORC, CCR6 and IL-23R transcript. Compared to conventional entheseal T-cells, MAITs expressed significantly less TGFβ (6-fold, p>0.001) and significantly more IL-23R (29-fold, p=0.004). Conclusion: Healthy human entheseal tissue contains an enriched population of MAITs that strongly express IL-23R transcript at a frequency comparable to that reported in the colon (2). The majority of these cells express a resident memory phenotype suggesting that they are a distinct population residing in entheseal tissue. These observations are potentially relevant to SpA pathogenesis and the observed link between SpA and IBD. References: [1] Gracey E, Qaiyum Z, Almaghlouth I, Lawson D, Karki S, Avvaru N, et al. IL-7 primes IL-17 in mucosal-associated invariant T (MAIT) cells, which contribute to the Th17-axis in ankylosing spondylitis. Annals of the rheumatic diseases. 2016:annrheumdis-2015-208902. [2] Salou M, Franciszkiewicz K, Lantz O. MAIT cells in infectious diseases. Current opinion in immunology. 2017;48:7-14. Disclosure of Interests: Richard Cuthbert: None declared, Qiao Zhou: None declared, Abdulla Watad: None declared, Robert Dunsmuir: None declared, Peter Loughenbury: None declared, Almas Khan: None declared, Peter Millner: None declared, Charlie Bridgewood: None declared, Dennis McGonagle Consultant for: Lilly, Novartis UCB, Speakers bureau: Lilly, Novartis UCB